Possibilities of downsizing sweet cherry trees via growing techniques - Király, Katalin (Acta Agraria Debreceniensis, 2005)
By applying smaller crown sizes and intensive growing techniques, many advantages can be identified compared to the extensive orchards. Also, nursing/pruning and harvest work can be performed more effectively. The outer and inner quality parameters of the fruit and the effectiveness of plant protection techniques are improved. The smaller crown size enables us to apply technologies for ensuring yield safety (e.g. hail, rain, bird nets), resulting in an increase in productivity. The introduction of smaller trees poses a great challenge to cherry production. Trials with dwarfing rootstocks have not yet been successful, therefore, we must use the cv. Mahaleb rootstock, which is excellently adapted to the Hungarian conditions, and also has a stronger growth. In addition, rootstocks with such strong growth are needed for the necessary regeneration of the productive parts of cherry cultivars, there is a need for. At the research garden of the University of Debrecen in Pallag, we planted 21 cherry cultivars on cv. Mahaleb (CT500) rootstock, in a 4 m x 1 m spacing pattern, in the spring of 2000. In our study, we demonstrated the possibilities of developing and maintaining the string super spindle through repeated summer pruning, in terms of growth, bud and fruit formation,. Based on these parameters, we determined which cultivars are the most suitable for intensive production.